Fabrication of aluminium doped zinc oxide piezoelectric thin ﬁlm on a silicon substrate for piezoelectric MEMS energy harvesters - Md Ralib @ Md Raghib, Aliza 'Aini; Nordin, Anis Nurashikin; Salleh, Hanim; Othman, Raihan (Springer Berlin / Heidelberg, 2012)
Thin film piezoelectric materials play an essential role in micro electro mechanical system (MEMS)energy harvesting due to its low power requirement and high available energy densities. Non-ferroelectric piezoelectric materials such as ZnO and AlN are highly silicon compatible making it suitable for MEMS energy harvesters in self-powered microsystems. This work primarily describe the design, simulation and fabrication of aluminium doped zinc oxide (AZO) cantilever beam deposited on \100[ silicon substrate. AZO was chosen due its high piezoelectric coupling coefficient, ease of deposition and excellent bonding with silicon substrate. Doping of ZnO with Al has improved the electrical properties, conductivity and thermal stability. The proposed design operates in transversal mode (d31 mode) which was structured as a parallel plated capacitor using Si/Al/AZO/Al layers. The highlight of this work is the successful design and fabrication of Al/AZO/Al on\100[silicon as the substrate to make the device CMOS compatible for electronic functionality integration. Design and finite element modeling was conducted using COMSOLTM software to estimate the resonance frequency. RF Magnetron sputtering was chosen as the deposition method for aluminium and AZO. Material characterization was performed using X-ray diffraction and field emission scanning electron microscopy to evaluate the piezoelectric qualities, surface morphology and the cross section. The fabricated energy harvester generated 1.61 V open circuit output voltage at 7.77 MHz resonance frequency.The experimental results agreed with the simulation results. The measured output voltage is sufficient for low power wireless sensor nodes as an alternative power sources to traditional chemical batteries